Rancang Bangun Sistem Informasi Perpustakaan Menggunakan Algoritma Apriori Dalam Penentuan Penempatan Buku Di SMAN 1 Warureja Kabupaten Tegal - Handayanto, Agung; Waliyansyah, Rahmat Robi; Irwanto, Muhammad Riyan (Utility Project Solution, 2022)
The library is one of the facilities provided by educational institutions as a support and support for the process of teaching and learning activities for students. In the process of collecting data on book transactions at the SMA N 1 Warureja library still using a manual database so that all transactions are still written on the book, the use of manual databases in accessing data will be slow and less efficient. In addition, placing books far apart causes students to take longer to find books when borrowing books of different types. To overcome these problems, the authors design and build a library information system using the a priori algorithm in determining the placement of books at SMA N 1 Warureja, Tegal Regency. In this study, the method used is an Object Oriented Program (OOP) approach using the Unified Modeling Language (UML), system development using the waterfall method and will utilize an a priori algorithm in determining book placement. The results of system testing are obtained from black box testing with the results of the existing system functions being 100% valid and 0% invalid. and UAT (User acceptance testing) with results that have a percentage of 90.29% in terms of usefulness, 93.33% in terms of interface appearance, and 98% in terms of use so that it can be concluded that the system is running as expected. In white-box testing, it was found that the result of complexity is 3. Suggestions that can be submitted are that the a priori algorithm method can be used as an alternative in determining the placement of books in the library.